ANALYSIS OF THE EFFECTS OF URBAN SPRAWL ON THE TRANSFORMATION OF PANGKALPINANG CITY - Mayasari, Dessy; I Gede Wyana Lokantara (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
The characteristics of Pangkalpinang City as an archipelagic area have undergone a spatial transformation. Historically, the Pangkalpinang City area has been a mining area since 1973, and is currently developing into the capital city of Bangka Belitung province. developed into the service sector, industry, and trade. This study aims to analyze the spatial transformation of Pangkalpinang City due to urban sprawl and the pattern of changes that occur. The methodology used in this study is a mix method consisting of several methods such as the city's economic development sector using Dynamic Location Queationt, socio-spatial analysis, and leapfrog analysis. This study found that several sub-districts in the Pangkalpinang City area experienced a leapfrog type of spatial development, which was characterized by the orientation of the development of residential and industrial areas. The land in Pangkalpinang City is not productive agricultural land, but dry land plantation areas, so that the development of urban physical expansion does not eliminate the essential benefits of agricultural land for food productivity. Meanwhile, under the ex-mines, currently it has been used for the development of the fishery sector and the use of renewable energy development. Another finding is that the limited space of Pangkalpinang City to support the growing development will result in the orientation of land use towards the surrounding suburbs